2005
DOI: 10.5558/tfc81104-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth intercept models for black spruce, jack pine and balsam fir in Quebec

Abstract: Site index has traditionally been estimated using height over age curves in the province of Quebec (e.g., Vézina and Linteau 1968, Boudoux 1978, Pothier and Savard 1998. While such curves tend to be effective tools for estimating site index in mature stands, they are unreliable for estimating site index in juvenile stands, i.e., stands that are younger than 20 years old at breast height (Nigh 1995). Conversely, variable growth intercept models are being increasingly used outside Quebec to give reliable site in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
(8 reference statements)
0
6
0
Order By: Relevance
“…Studies by Mallik (2003) and Ruel et al (2004) and a summarizing paper by Rheault (2013) have shown that, at higher latitudes in eastern Canada (>48°N), naturally regenerating black spruce take, on average, 25 years to reach the sapling stage of 100 cm. Omitting this time period likely has important consequences for expected harvest volumes (Sims et al 1990;Mailly and Gaudreault 2005): forest productivity is usually rated with site index (SI) curves that are based on measurements taken at a stem height of 100 or 130 cm. Therefore, if a SI curve suggests a total period of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Studies by Mallik (2003) and Ruel et al (2004) and a summarizing paper by Rheault (2013) have shown that, at higher latitudes in eastern Canada (>48°N), naturally regenerating black spruce take, on average, 25 years to reach the sapling stage of 100 cm. Omitting this time period likely has important consequences for expected harvest volumes (Sims et al 1990;Mailly and Gaudreault 2005): forest productivity is usually rated with site index (SI) curves that are based on measurements taken at a stem height of 100 or 130 cm. Therefore, if a SI curve suggests a total period of ca.…”
Section: Introductionmentioning
confidence: 99%
“…Methods, such as the one proposed by Mailly and Gaudreault (2005) might be more promising in predicting the long-term yield of boreal plantations on an annual basis. The paraboloid power function (Forslund and Paterson 1994) seems to be a good method for evaluating the total volume at a given age with few measurements.…”
Section: Discussionmentioning
confidence: 99%
“…The site index was calculated using the method of Nigh (1997), but setting the reference height for age at 1.0 m (Mailly and Gaudreault 2005). The site index was thus obtained by calculating the top height reached at the time of sampling and the age determined at 1.0 m. Growth intercepts were calculated using the equations presented by Mailly and Gaudreault (2005) for each age 100 from one to the last year measured in given stands. Site index values in Table 2 refer to the calculation at the age of sampling.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relationships between jack pine growth and site variables were reported for plantations in New Brunswick using the growth intercept approach (Hamilton and Krause 1985). Recently, GI models were developed for natural young stands of black spruce, jack pine, and balsam fir in Quebec (Mailly and Gaudreault 2005). In Ontario, GI models had been developed for white spruce plantations (Thrower 1987), jack pine (Guo and Wang 2006) and black spruce plantations (M. Kwaiton and J. Wang, Lakehead University, unpublished data).…”
Section: Site Index/interceptmentioning
confidence: 99%